Effectiveness of Stress Inoculation Training on Emotional Regulation, Childbirth Self-Efficacy and Natural Childbirth Anxiety - Masihpour Mojavery, Omolbanin; Abbasi, Ghodratollah; Moslemi, Leila (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to examine the effectiveness of stress inoculation training on emotional regulation, Childbirth Self-Efficacy and natural childbirth anxiety in pregnant women. Methods: This study employed a quasi-experimental design with a pre-test–post-test and a control group. The sample was selected using convenience random sampling, and 45 pregnant women experiencing natural childbirth anxiety were recruited from healthcare centers. Participants were randomly assigned to three groups (two experimental groups and one control group). The experimental groups received stress inoculation training, while the control group did not receive any intervention. The research instrument included the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) (Wijma et al., 1998), which was administered during the pre-test and post-test phases across all three groups. Findings: The results indicated that stress inoculation training had a significant effect on reducing natural childbirth anxiety and increasing positive emotional regulation and childbirth self-efficacy, while negative emotional regulation decreased among women in the experimental groups. Conclusion: Stress inoculation training can be utilized as an effective approach to reducing anxiety and improving emotional regulation and self-efficacy in pregnant women with natural childbirth anxiety, thereby promoting mental health and facilitating a more positive childbirth experience.